Practice Patterns and Patient Outcomes After Widespread Adoption of Remote Heart Failure Care. (October 2021) - Yuan, Neal; Botting, Patrick G.; Elad, Yaron; Miller, Shaun J.; Cheng, Susan; Ebinger, Joseph E.; Kittleson, Michelle M.
Abstract : Background: An unprecedented shift to remote heart failure outpatient care occurred during the coronavirus disease 2019 (COVID-19) pandemic. Given challenges inherent to remote care, we studied whether remote visits (video or telephone) were associated with different patient usage, clinician practice patterns, and outcomes. Methods: We included all ambulatory cardiology visits for heart failure at a multisite health system from April 1, 2019, to December 31, 2019 (pre-COVID) or April 1, 2020, to December 31, 2020 (COVID era), resulting in 10 591 pre-COVID in-person, 7775 COVID-era in-person, 1009 COVID-era video, and 2322 COVID-era telephone visits. We used multivariable logistic and Cox proportional hazards regressions with propensity weighting and patient clustering to study ordering practices and outcomes. Results: Compared with in-person visits, video visits were used more often by younger (mean 64.7 years [SD 14.5] versus 74.2 [14.1]), male (68.3% versus 61.4%), and privately insured (45.9% versus 28.9%) individuals ( P <0.05 for all). Remote visits were more frequently used by non-White patients (35.8% video, 37.0% telephone versus 33.2% in-person). During remote visits, clinicians were less likely to order diagnostic testing (odds ratio, 0.20 [0.18–0.22] video versus in-person, 0.18 [0.17–0.19] telephone versus in-person) or prescribe β-blockers (0.82 [0.68–0.99], 0.35 [0.26–0.47]), mineralocorticoid receptor antagonists (0.69 [0.50–0.96], 0.48 [0.35–0.66]), or loop diuretics (0.67 [0.53–0.85], 0.45 [0.37–0.55]). During telephone visits, clinicians were less likely to prescribe ACE (angiotensin-converting enzyme) inhibitor/ARB (angiotensin receptor blockers)/ARNIs (angiotensin receptor-neprilysin inhibitors; 0.54 [0.40–0.72]). Telephone visits but not video visits were associated with higher rates of 90-day mortality (1.82 [1.14–2.90]) and nonsignificant trends towards higher rates of 90-day heart failure emergency department visits (1.34 [0.97–1.86]) and hospitalizations (1.36 [0.98–1.89]). Conclusions: Remote visits for heart failure care were associated with reduced diagnostic testing and guideline-directed medical therapy prescription. Telephone but not video visits were associated with increased 90-day mortality. Abstract : Supplemental Digital Content is available in the text.